The Influence of Regulated Marital Conflict Resolution Styles on Marital Stability in Kiambu County, Kenya - Njoroge, Sarah (European Scientific Journal, ESJ, 2017)
The purpose of the study was to establish the relationship between regulated conflict resolution styles and marital stability in Kiambu County, Kenya. Specifically, the study sought to: establish the types of marital conflicts among married individuals in Kiambu County; determine the various marital conflict resolution styles used by married individuals in the County, and; establish the relationship between marital conflict resolution styles and marital stability. Descriptive-correlation research design was used. Data was collected from 96 married individuals aged 18 years and above by aid of a structured questionnaire. Data analysis was carried out using SPSS. The statistical techniques applied included independent samples T-test, Chisquare and Mann-Whitney U test. The results showed that most types of conflicts were solvable. Descriptive statistics indicated that regulated marital conflict resolution styles were used by majority of the respondents, with validating styles being the most applied (M=2.87, SD=0.745). This was followed by volatile styles (M=2.79, SD=0.827) and avoidant styles (M=2.79, SD=0.739). The difference between individuals in stable marriages and those in unstable marriages was not statistically significant in terms of their use of regulated marital conflict resolution styles. It was concluded that regulated conflict resolution styles were a necessary but not sufficient conditions for marital stability. It was recommended that premarital counselors should highlight to the would be couples that some conflicts are perpetual and therefore require coping with, rather than resolving.